The right to rights and Central American/Mexican migration films: Reading Sin nombre (Fukunaga 2009) and La jaula de oro/The Golden Dream (Quemada-Díez 2013) with political theory. Issue 3 (1st September 2021) - Shaw, Deborah
In this article, I argue in favour of using political and social theory as a framework for reading Central American and Mexican migration films, using Sin nombre (Fukunaga 2009) and La jaula de oro/The Golden Dream (Quemada-Díez 2013) as case studies. Key ideas of Hannah Arendt, Giorgio Agamben, Zygmunt Bauman and Judith Butler can yield important insights when applied to the readings of migration films. My particular interest here is their conceptualizations of the scale of value applied to human life, and the resulting right to rights, or failure to be granted rights, as this is particularly apposite to the condition of migrants and refugees and to the role of film in creating value. A central argument is that film has a specific role in challenging or endorsing the negative values placed on the lives of migrant/refugees in hegemonic political and media discourses. I claim that cinema has the ability to create Arendtian personae, particularly important as in the political and media discourses around refugees and migrants the embodied experiences of refugee‐migrants themselves are frequently absent. La jaula de oro presents a textual and extra-textual call for the right to rights for its non-citizen migrant characters. Yet, film also has the potential to support prevailing fears and stereotypes, and work against Arendt's concept of the right to rights, and I argue that Sin nombre runs the risk of endorsing this position.